Tax-induced earnings management: Analyzing the impact of profitability, deferred tax assets, and tax planning strategies - Pahala, Indra; Purwohedi, Unggul; Haryani, Putri; Prihatni, Rida; Hasanah, Alifa Shafiya Nur (International Journal of Innovative Research and Scientific Studies, 2025)
This research uses a quantitative approach to analyze data from 22 companies in the property and real estate sector listed on the Indonesia Stock Exchange (IDX) during the period 2020-2022. The study aims to examine the effect of profitability, deferred tax assets, current tax expenses, and tax planning on earnings management. The results reveal that profitability has a negative and significant effect on earnings management, while deferred tax assets and tax planning show a negative but insignificant effect. Current tax expenses, on the other hand, have a positive and significant effect on earnings management. Furthermore, the model feasibility test indicates that profitability, deferred tax assets, current tax expenses, and tax planning collectively influence earnings management. These findings suggest that while profitability and current tax expenses play significant roles in earnings management, deferred tax assets and tax planning may not have as substantial an impact, offering practical implications for companies to focus on managing profitability and current tax expenses effectively in influencing their earnings management practices.